2018
DOI: 10.1186/s12936-018-2415-1
|View full text |Cite
|
Sign up to set email alerts
|

Community-based malaria control in southern Malawi: a description of experimental interventions of community workshops, house improvement and larval source management

Abstract: BackgroundIncreased engagement of communities has been emphasized in global plans for malaria control and elimination. Three interventions to reinforce and complement national malaria control recommendations were developed and applied within the context of a broad-based development initiative, targeting a rural population surrounding a wildlife reserve. The interventions, which were part of a 2-year research trial, and assigned to the village level, were implemented through trained local volunteers, or ‘health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 34 publications
4
93
0
Order By: Relevance
“…Therefore, aquatic habitats are important for mosquito breeding. Larval source management (LSM) involves the management of water bodies that are potential larval habitats to prevent the development of immature mosquitoes into adults [18,19], and studies have shown that mosquito LSM has an important potential impact on mosquito-borne disease transmission both in urban and rural areas [20][21][22]. For example, in urban areas of Dar es Salaam, Tanzania, the use of larvicides reduced the risk of malaria infection in 5-year-old children [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aquatic habitats are important for mosquito breeding. Larval source management (LSM) involves the management of water bodies that are potential larval habitats to prevent the development of immature mosquitoes into adults [18,19], and studies have shown that mosquito LSM has an important potential impact on mosquito-borne disease transmission both in urban and rural areas [20][21][22]. For example, in urban areas of Dar es Salaam, Tanzania, the use of larvicides reduced the risk of malaria infection in 5-year-old children [23].…”
Section: Introductionmentioning
confidence: 99%
“…The Health Animation model is a community engagement approach used to promote positive health behaviour for disease control. This is supposed to be achieved by focusing on influencing a mindset of understanding the threat of disease and promoting positive health seeking behaviours [10,18]. This involves the provision of information through peer-led health education and communication of diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…This involves the provision of information through peer-led health education and communication of diseases [10]. The HA approach was pioneered and is promoted by the non-governmental organization, The Hunger Project (THP), for awareness and prevention of disease in developing countries [10,18]. This concept works within THP's larger framework of community development through collective accountability and action [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations